ANALISIS FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP LUAS PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Bella Arika Phonna, 12.05.52.0010; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2016)
This study aims to determine the effect of profitability (ROE), Independent Commissioner Board Size, Leverage, Size and institutional ownership, public ownership, and the liquidity of the disclosure of Corporate Social Responsibility area companies including food and beverage categories listed in the Indonesia Stock Exchange. The population is all food and beverage company in the Indonesia Stock Exchange in 2010 - 2014. The sampling technique used was purposive sampling. The analytical tool used in this research is Multiple Regression Analysis Partial results of this study show the public ownership of significant positive effect on disclosure of CSR while variable profitability, independent board size, leverage size, Institutional ownership and liquidity does not affect the broad disclosure of CSR.Keywords: Profitability, Comissioner Independent Size, Leverage Size, Institutional Ownership, Public Ownership, Liquidity, CSR Disclosure